Alkalized MXene-supported nanoscale zero-valent iron in situ derived from NH2-MIL-88B(Fe) for the highly efficient catalytic reduction of 4-nitrophenol. (June 2022) - Zhang, X.; Sun, H.; Huang, J.; Zheng, Q.; Zhang, F.; Li, H.; Zhang, M.; Zeng, J.; Yan, Z.
Abstract: Nanoscale zero-valent iron (nZVI) is widely used to remove environmental pollutants. However, it is a great challenge to prepare non-agglomerated and stable nZVI due to its strong magnetism and high activity. Herein, we prepared alkalized MXene-supported nZVI (nZVI@Alk-Ti3 C2 ) that was in situ derived from NH2 -MIL-88B(Fe) and investigated its catalytic performance during the reduction of 4-nitrophenol (4-NP) with NaBH4 . It is found that compared with the unsupported nZVI, the nZVI@Alk-Ti3 C2 composite exhibited excellent catalytic activity and stability after ten cycles of reaction due to the uniform distribution of nZVI on Alk-Ti3 C2 with an average diameter of 39 nm and the synergistic effect between nZVI and Alk-Ti3 C2 . In addition, the organic ligands NH2 -BDC were anchored on the surface of nZVI derived from Fe-MOFs, which facilitated the enrichment of 4-NP and subsequently increased the effective contact between the reactants and active sites. nZVI@Alk-Ti3 C2 is considered to be an eco-friendly, efficient, and promising catalyst for 4-NP wastewater treatment. Graphical abstract: Image 1 Highlights: Alkalized MXene-supported nZVI was in situ derived from Fe-MOFs. NZVI was highly dispersed on Alk-Ti3 C2 . NZVI@Alk-Ti3 C2 exhibited excellent catalytic performance and stability. The synergistic effect between nZVI and Alk-Ti3 C2 enhanced catalytic efficiency.